Inhibitory activity of garlic (Allium sativum) extract on multidrug-resistant Streptococcus mutans - Fani M; Kohanteb J; Dayaghi M (Wolters Kluwer Medknow Publications, 2007)
Garlic ( Allium sativum ) extract has been known to have inhibitory activity on various pathogenic bacteria, viruses and fungi. The objective of present investigation was to study in vitro inhibitory activity of garlic extract on multidrug-resistant (MDR) strains of Streptococcus mutans isolated from human carious teeth. Filter sterilized aqueous extract of garlic was prepared and used in the present study. For isolation of S. mutans , extracted human carious teeth were cultured in Todd-Hewit broth and Mitis-Salivarius-Bacitracin agar. S. mutans was characterized by colony morphology, biochemical tests and other conventional bacteriological procedures. Disk sensitivity tests and broth dilution methods were used to determine antibiotic sensitivity profile and inhibitory activity of garlic extract on S. mutans isolated from carious teeth. Of 105 carious teeth tested, 92 (87.6%) isolates of S. mutans were recovered, among which 28 (30.4%) were MDR since they were resistant to four or more antibiotics. The highest rate of resistance was observed for tetracycline (30.4%) and least resistance (0%) to teichoplanin and vancomycin while 22.8% and 23.9% of the isolates were resistant to penicillin and amoxicillin, respectively. Chlorhexidine minimum inhibitory concentration (MIC) for MDR and non-MDR S. mutans varied from 2 to 16 µg ml−1 and from 0.25 to 1 µg ml−1 , respectively ( P < 0.05). All isolates, MDR and non-MDR of S. mutans were sensitive to garlic extract with the MIC ranging from 4 to 32 mg ml−1 . Considering in vitro data obtained in the present study, mouthwashes or toothpaste containing optimum concentration of garlic extract could be used for prevention of dental caries.